استخدام الوسيلة التعليمية يوتيوب لتعليم مهارة الاستماع بالصف الأول في المدرسة الابتداية: استخدام الوسيلة التعليمية يوتيوب لتعليم مهارة الاستماع بالصف الأول في المدرسة الابتداية - Moh Syaifudin (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2021)
The educational medium becomes a tool to facilitate study in this era of 4.0, the use of technology is an important matter and an integral part of the education process. The use of the YouTube platform is one of the modern methods used in the education process. YouTube is a process that has been developed to become a new method of teaching Arabic, specific and clear. It is the most powerful and most popular Web 2.0 application on the Internet, and although most people use it for entertainment, YouTube can be an effective and useful educational tool, whether in research, or educational presentations. The YouTube educational tool can be used by watching the available channels with many visuals related to the topics and walking towards the curriculum so that students can acquire the Arabic language and develop their language skills, especially listening skill. Listening is one of the four important language skills today. It is considered an important receptive skill that is targeted by every linguistic study curriculum. In this way, the learning process of the Arabic language will be filled with joy and away from boredom